The emergence and loss of cyclic peptides in Nicotiana illuminate dynamics and mechanisms of plant metabolic evolution - Elliot M. Suh; Jakob K. Reinhardt; Jing-Ke Weng (Proceedings of the National Academy of Sciences, 2025)
Specialized metabolism plays a central role in how plants cope with both biotic and abiotic stresses in order to survive and reproduce within dynamic and challenging environments. One recently described class of plant-specific, ribosomally synthesized, and posttranslationally modified peptides are the burpitides, which are characterized by the installation of distinct sidechain macrocycles by enzymes known as burpitide cyclases. While they are found across many plant families and exhibit diverse bioactivities, little is known about their evolution or how new variants arise. Here, we present the identification of a burpitide cyclase, resurrected from a defunct pseudogene from the model organism Nicotiana attenuata , the coyote tobacco. By repairing the pseudogene ΨNatBURP2 and expressing it heterologously in Nicotiana benthamiana , we successfully reconstituted its original enzymatic activity. As an autocatalytic peptide cyclase, it installs a unique C–C bond between the tyrosine side chain and a specific backbone α-carbon of a heptapeptide core motif, resulting in burpitides dubbed “nanamins.” Despite its pseudogenization in N. attenuata , we found that the closely related species, Nicotiana clevelandii , retains the wild-type gene and produces nanamins. Phylogenetic analyses and targeted mutagenesis experiments reveal that this chemotype must have evolved from the duplication and neofunctionalization of a more promiscuous ancestral gene. This work highlights how novel peptide chemotypes may rapidly emerge and disappear in plants, while expanding the molecular toolkit for engineering novel peptides with applications in agriculture and drug discovery.